Problems of determination of the «administrative opinionika» in the system of jurisprudence - Беззубов, Дмитро Олександрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The paper considers the problem of the «administrative opinionika» determination in the system of jurisprudence. It reveals the essence of the problems of administrative law as an essential component of the public safety ensuring. Also the author identifies categories of administrative law sociology and «administrative opinionika». One of the actual directions of the administrative law development is studying of the problems of providing of the public safety by the methods of administrative activity that are used by the organs of executive power. Further development of the administrative law in the field of providing of the public safety and activity of the organs of executive power can lead to appearance of the new science - administrative opinionika.